Protection of computer-generated works in the era of new technologies - Ingrida Veiksa (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
When data on works of different authors are entered into a computer system, the computer analyses, synthesizes and generates a new (derived) work, if such a task or algorithm is given to it. Should computer generated works be considered creative and copyright protected? This issue is relevant in the modern age of technology, when computer systems, the so-called artificial intelligence, are becoming more independent from human influence as they evolve.